If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying J + -1.2(0.4 + -0.1j) = 2.88 J + (0.4 * -1.2 + -0.1j * -1.2) = 2.88 J + (-0.48 + 0.12j) = 2.88 Reorder the terms: -0.48 + J + 0.12j = 2.88 Solving -0.48 + J + 0.12j = 2.88 Solving for variable 'J'. Move all terms containing J to the left, all other terms to the right. Add '0.48' to each side of the equation. -0.48 + J + 0.48 + 0.12j = 2.88 + 0.48 Reorder the terms: -0.48 + 0.48 + J + 0.12j = 2.88 + 0.48 Combine like terms: -0.48 + 0.48 = 0.00 0.00 + J + 0.12j = 2.88 + 0.48 J + 0.12j = 2.88 + 0.48 Combine like terms: 2.88 + 0.48 = 3.36 J + 0.12j = 3.36 Add '-0.12j' to each side of the equation. J + 0.12j + -0.12j = 3.36 + -0.12j Combine like terms: 0.12j + -0.12j = 0.00 J + 0.00 = 3.36 + -0.12j J = 3.36 + -0.12j Simplifying J = 3.36 + -0.12j
| 0.4x=60 | | Bx+9=3y | | 5y+20=7x-56 | | x/5-7/4=x/10-1/20 | | -6n-5n=-16-7n | | 9/22=x/176 | | Ar=3r+14 | | 34=x/64 | | 63-f=52 | | K-8=5k-k-5 | | .2I+4(.3+.2I)=2.2 | | 14x+2=9x+20 | | 0.1x+0.2x=6 | | -(12-t)+(2t-4)= | | 17*v/v=7 | | 13/21=x/147 | | 6(x+9)=60 | | 1+2r-r=11+3r | | 12*c=156 | | 4y=-6+4x | | 1+1+5x-8=5x+x | | 90=(x-2)(y-1.5) | | 12/5=x/45 | | (4i)(-8+8i)= | | 5.3x=4.1x+5.76 | | 2.5h+.5(h-1)=-12.5 | | 5x-9=-3x+12+5x | | 7/12=x60 | | 1/8x-9=17 | | 3x+6=8x-49 | | 2x-3(5-3x)=7x+3 | | .3+.2(g+7)=1.5 |